Effects of high organic load on amoA and nirS gene diversity of an intermittently aerated and fed membrane bioreactor treating landfill leachate. (November 2016) - Remmas, Nikolaos; Melidis, Paraschos; Katsioupi, Efthymia; Ntougias, Spyridon
Highlights: amoA and nirS gene dynamics were examined in a MBR treating landfill leachate. High organic load inhibited ammonia oxidation, resulting in ammonia accumulation. Nitrosomonas was highly affected, while Nitrosospira showed a degree of tolerance. Massive shift in denitrifiers occurred, detecting nirS found in NH3 -rich effluents. Thauera - and Acidovorax -related nirS genotypes became predominant. Abstract: The effects of external carbon source addition on the nitrification and denitrification process were investigated in an intermittently aerated and fed membrane bioreactor treating landfill leachate by recording system performance, and amoA and nirS diversity dynamics using pyrosequencing. By adding 950 mg/L glycerol, denitrification was optimized, resulting in total nitrogen removal efficiency of 81.0 ± 2.4%. Under these conditions, amoA diversity was dominated by genotypes related to Nitrosomonas europaea, while increase in leachate's content and in glycerol addition by 50% led to irreversible inhibition of nitrification and enhanced ammonia accumulation, causing a severe suppression of Nitrosomonas and an increase in the relative abundance of Nitrosospira . However, this increase not only affected ammonia oxidizers, but also caused a massive shift in denitrifying community structure, resulting in the suppression of Arenimonas metalli -, Candidatus Accumulibacter- and Sulfuritalea hydrogenivorans - nirS related genotypes and the predominance of nirS -associated with Acidovorax and Thaurea sp.